Water Control System at Water Depot With Water Flow Sensor - Muhammad Imam Ghozali Imam; M. Bachrul Ulum Firmansyah; Wibowo Harry Sugiharto (Jurnal Mantik, 2022)
Water is an important component for living on Earth, the presence of fresh water on land makes humans think long term to anticipate the worst possibility in the future, drought. Freshwater currently available has several uses, such as for toilets and kitchen needs, specifically for kitchen needs, the water consumed must be processed, so that the microorganisms contained in the water die, so that they are not dangerous when consumed. One of the steps for treating raw freshwater is so that the consumption screen can do it in one way, filtering. In most water depots currently using this method, the process includes water from a holding tank at the pump and then temporarily stored in a settling tank that has been pressurized O3 (Ozone), then the water enters a filtering tank containing a filter to prevent foreign substances from entering carried away by water, the last water will flow through an ultraviolet light filter to kill microorganisms and in the final stage, the water is ready for consumption. The use of water flow sensors and Arduino microcontrollers at this water depot is to control the use of water per gallon, thereby reducing wasted water when the gallon is slightly tilted.